An imaging interferometry capability for the EISCAT Svalbard Radar - Grydeland, T.; Chau, J. L.; La Hoz, C.; Brekke, A. (Annales Geophysicae, 2005)
Interferometric imaging (aperture synthesis imaging) is a technique used by radio astronomers to achieve angular resolution that far surpasses what is possible with a single large aperture. A similar technique has been used for radar imaging studies of equatorial ionospheric phenomena at the Jicamarca Radio Observatory. We present plans for adding an interferometric imaging capability to the EISCAT Svalbard Radar (ESR), a capability which will contribute significantly to several areas of active research, including naturally and artificially enhanced ion-acoustic echoes and their detailed relation in space and time to optical phenomena, polar mesospheric summer echoes (PMSE), and meteor studies. Interferometry using the two antennas of the ESR has demonstrated the existence of extremely narrow, field-aligned scattering structures, but having only a single baseline is a severe limitation for such studies. Building additional IS-class antennas at the ESR is not a trivial task. However, the very high scattering levels in enhanced ion-acoustic echoes and PMSE means that a passive receiver antenna of more modest gain should still be capable of detecting these echoes. In this paper we present simulations of what an imaging interferometer will be capable of observing for different antenna configurations and brightness distributions, under ideal conditions, using two different image inversion algorithms. We also discuss different antenna and receiver technologies.